EMMANUEL EYO’S ‘JESUS CHRIST THE PHILOSOPHER: AN EXPOSÉ’ AND THE MISSING LINK OF METAPHYSICS - John Gabriel Mendie (Universitas Negeri Makassar, 2020)
This paper recaps at first duty Eyo, Emmanuel Bassey’s article on ‘Jesus Christ the Philosopher: An Exposé’ which he exposes different areas of philosophy where the teaching of Jesus Christ could be attributed. The work raises arguments in reaction to the neglect of Metaphysics as an important area of Jesus’ philosophy. The author may have presumed that Metaphysics falls within the ambience of religion and theology and looks at Jesus as a historic person. The main concern of this paper therefore, is to examine the person and teachings of Jesus which are metaphysical. This paper further argued that the concept of metaphysics is promising as it studies the totality of reality, however, it is not error-proof as it has its inherent lacuna. In this paper I employ the methods of dialectic analysis and complementary fusion.